Safeguarding children and young people : a guide for professionals working together - Frost, Nick, 1960- (London Sage, 2021)
"Safeguarding Children and Young People offers students and practitioners an accessible and multi-disciplinary guide to working together with other professionals to deliver a child-centred and co-ordinated approach to safeguarding, in line with the Working Together to Safeguard Children guidance. Taking a 'whole systems' approach, and offering support on prevention, assessment, intervention, systems, and leadership, the book reflects on recent challenges including contextual abuse, child sexual exploitation and cyber-abuse. The book includes case studies, activities and points for reflection to aid learning and test understanding"--
Keywords: Social work with children; Child abuse -- Prevention